The Association Between Environmental Factors and Scrub Typhus: A Review - Shu Yang; Shu Yang; Yuxiang Xie; Wenjing Duan; Yiting Cui; Ai Peng; Yisheng Zhou; Yibing Fan; Hui Li; Peng Huang (Tropical Medicine and Infectious Disease, 2025)
Scrub typhus is an acute febrile vector-borne infectious disease caused by Orientia tsutsugamushi (O. tsutsugamushi) and transmitted through the bite of infected chigger mite larvae. Transmission involves complex ecological interactions among vectors, hosts, and environmental factors. Accumulating evidence indicates complex interactions between the scrub typhus incidence and multilevel environmental determinants, encompassing meteorological factors (e.g., temperature, humidity, precipitation, wind speed, sunshine duration, and atmospheric pressure), geographical conditions (e.g., topography, elevation, and landcover), and socioeconomic factors (e.g., economic level, cultural practices, residential conditions, and human behaviors). However, significant discrepancies persist among studies regarding the effect sizes and temporal associations, and the precise mechanisms remain incompletely elucidated. This review synthesizes the evidence on environment–disease relationships, clarifies the methodological inconsistencies, analyzes the potential sources of heterogeneity, and highlights the critical knowledge gaps to inform targeted prevention and control strategies and guide future research priorities.